Os impactos das macromudanças da saúde suplementar: um estudo de caso da CAMED - VIANA FILHO, Osvaldo (2013)
The health care market in Brazil, according to data from the National Health Agency (ANS), until December 2012 watched 47,9 million people and handled funds of R$ 95 billion (ANS – 2013). So, this research focused on the controlling of this important sector of the economy as well as in organizational change created from this process. Based on the information before, this dissertation aims to analyze the health care market in Brazil before and after the controlling, and to understand how the supplemental Health macro-changes filled up the dynamics of organizational units of analysis of this empirical research calls the Assistance Fund of the Employees of BNB (Camed). This a single instance study, which used as a methodological strategy the Collective Subject Discourse (CSD), by semi-structured interviews, which allowed us, by means quantitative-quality, together with the studying of other findings the understanding of the phenomenon, give the challenges of their singularity and contemporary. As a result, CAMED faced a big process of structural changes both voluntary as responsive, which influenced on its dynamic, resulting in changes in its coorporative strategy, structure and technology, sum with more professionals. Those changes provided CAMED to become not only a health self-management operator in medical group, but also an expert in Collaborative health care management grateful to its participatory nature and re-education.